A complete folk theorem for finitely repeated games - Ghislain H. Demeze-Jouatsa (Bielefeld University, Center for Mathematical Economics (IMW), 2018)
I analyze the set of pure strategy subgame perfect Nash equilibria of any finitely repeated game with complete information and perfect monitoring. The main result is a complete characterization of the limit set, as the time horizon increases, of the set of pure strategy subgame perfect Nash equilibrium payoff vectors of the finitely repeated game. The same method can be used to fully characterize the limit set of the set of pure strategy Nash equilibrium payoff vectors of any the finitely repeated game.
urn:nbn:de:0070-pub-29303825
Keywords: C72; C73; 330; Finitely Repeated Games; Pure Strategy; Subgame Perfect Nash Equilibrium; Limit Perfect Folk Theorem; Discount Factor